RESEARCH ON THE QUALITY OF ESSENTIAL OILS - Барус, Маріанна; Скрипська, Ольга; Ончуленко, Марія (SWorldJournal, 2025)
This article provides information on the chemical composition, biological activity and application of some types of essential oils, describes the results of the analysis of essential oil samples. The purpose of the study is to determine the quality and co